High-Latitude Gravity Wave Measurements in Noctilucent Clouds and Polar Mesospheric Clouds - Taylor, Michael J.; Pautet, P. D.; Zhao, Y.; Randall, C. E.; Lumpe, J.; Bailey, S. M.; Carstens, J.; Nielsen, K.; Russell III, J. M.; Stegman, J. (Hosted by Utah State University Libraries, 2010)
Distinct wave forms traditionally observed in Noctilucent Cloud (NLC) photographs and most recently captured in high-resolution panoramic images of Polar Mesospheric Clouds (PMC) provide an exceptionally rich resource for quantifying gravity wave activity and properties in the high-latitude summer mesopause region. Using extensive image data on PMC structures obtained by the Cloud Imaging and Particle Size (CIPS) ultraviolet instrument onboard the NASA Aeronomy of Ice in the Mesosphere (AIM) satellite, we have investigated the properties of prominent quasi-monochromatic waves imaged over the northern hemisphere polar region during summer 2007. Our two-dimensional spectral analysis has focused on the peak season, July period and over 450 events have been measured. The PMC field was found to contain a broad spectrum of gravity waves with horizontal wavelengths ranging from at least 20–400 km. The smallest scale wave events (km), exhibit the highest occurrence frequency, but substantial evidence for larger-scale (>100 km) wave activity was also found. The direction of motion of the waves (both large and small-scale) deduced from their orientations (with 180° ambiguity) was predominantly zonal (with a small meridional component), and differed significantly from recent NLC Type II band measurements which were dominated by strong near poleward wave motions. Evidence was also found for a reduction in gravity wave activity over the Europe/North Atlantic sector during the July 2007 period, as compared to other longitudes. These results build significantly on an initial seasonal investigation of quasi-monochromatic events by Chandran et al. (2009), and further demonstrate the high potential of CIPS data for detailed gravity wave studies. A more comprehensive investigation of the strong spatial alignments of the wave events and their longitudinal variability is currently in progress.